PENGARUH PROFITABILITAS DAN KOMPENSASI RUGI FISKAL TERHADAP TAX AVOIDANCE PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR LOGAM&SEJENISNYA YANG TERDAFTAR DI BEI PERIODE 2018–2021 - Angel Maria Grace,; Ronny Buha Sihotang, (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
The aim of conducting research is to find out the effect of profitability with fiscal loss compensation on tax avoidance of manufacturing companies in the metal & similar sub-sectors on the Indonesia Stock Exchange for the 2018-2021 period. It was determined through the purposive sampling method that there were around 36 samples from 17 selected companies. Using data in statistical form through the SPSS 25 application. The research results obtained are profitability and fiscal loss compensation have a simultaneous impact on tax evasion. The partial test obtains a significant effect on profitability, while compensation for fiscal losses does not have a significant effect on tax evasion.